Systemic and respiratory oxidative stress in the pathogenesis and diagnosis of Rhodococcus equi pneumonia. (December 2013) - Crowley, J.; Po, E.; Celi, P.; Muscatello, G.
Summary: Reasons for performing study: Oxidative stress (OS) is most simply defined as an imbalance between oxidants and antioxidants. Oxidative stress has been suggested to play roles in various equine respiratory diseases and the significance of OS in the pathogenesis of Rhodococcus equi pneumonia is unknown. Objectives: To measure and relate biomarkers of OS to lesions consistent with R. equi pneumonia. Study design: Case–control study. Methods: Various OS biomarkers were measured from blood and exhaled breath condensate (EBC) samples collected from 26 foals between 1 and 2 months of age (n = 12 cases and n = 14 controls) on 2 Thoroughbred farms endemically affected by R. equi pneumonia. Foals were defined as cases (positive) or controls (negative) based on ultrasonographic evidence of pulmonary abscessation (>15 mm in diameter). Haematology and biochemistry testing was also performed on blood samples collected from the foals. Comparison of biomarkers and key haematological and biochemical markers of inflammation between the groups was performed using 2 sample t tests. Results: Derivatives of reactive oxygen metabolites (d‐ROMs) were significantly greater in case foals than in control foals (P = 0.027) and the oxidative stress index (OSI) was higher in case foals (P = 0.014). Hydrogen peroxide (H2 O2 ) concentrations in EBC were significantly greater in case foals than in control foals (P = 0.002). Meanwhile, there were no significant differences in traditional measures of inflammation between the 2 groups. Conclusions: Measuring OS in both blood and EBC provided useful information in the early diagnosis of R. equi pneumonia.